2017
DOI: 10.1140/epje/i2017-11604-7
|View full text |Cite
|
Sign up to set email alerts
|

What experiments on pinned nanobubbles can tell about the critical nucleus for bubble nucleation

Abstract: Abstract. The process of homogeneous bubble nucleation is almost impossible to probe experimentally, except near the critical point or for liquids under large negative tension. Elsewhere in the phase diagram, the bubble nucleation barrier is so high as to be effectively insurmountable. Consequently, there is a severe lack of experimental studies of homogenous bubble nucleation under conditions of practical importance (e.g., cavitation). Here we use a simple geometric relation to show that we can obtain informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 28 publications
2
16
0
2
Order By: Relevance
“…Although P in changes sensitively with the bubble size r according to the Laplace equation, our simulations demonstrate that the determined p solvent is almost independent with r (see Figure a). The surface tensions for different nanobubbles were also determined from our MD simulations and shown in Figure b, and again it seems to be independent on the curvature radius of nanobubbles r , consistent with the general knowledge that the surface tension will be effected only for very small curve radii of a few nanometers …”
Section: Resultssupporting
confidence: 86%
“…Although P in changes sensitively with the bubble size r according to the Laplace equation, our simulations demonstrate that the determined p solvent is almost independent with r (see Figure a). The surface tensions for different nanobubbles were also determined from our MD simulations and shown in Figure b, and again it seems to be independent on the curvature radius of nanobubbles r , consistent with the general knowledge that the surface tension will be effected only for very small curve radii of a few nanometers …”
Section: Resultssupporting
confidence: 86%
“…Understanding the stability and the dynamics of surface nanobubbles, gaseous nanoscopic entities attached to hydrophobic surfaces, is relevant from both a fundamental and an applicational point of view. A single surface nanobubble will remain stable, provided a sufficient gas oversaturation in the bulk liquid and pinning of the three phase contact line. Lohse and Zhang showed that the equilibrium contact angle is not dictated by Young’s law, but by the expression: where L is the fixed (due to pinning) diameter of the footprint (assumed to be spherical) and L c = 4γ/ P 0 is the capillary length scale, γ is the surface tension, and P 0 is the ambient pressure. Furthermore, in expression , is the gas oversaturation, C ∞ is gas concentration in the bulk liquid, and C s is the saturation concentration at pressure P 0 .…”
mentioning
confidence: 99%
“…Stabilising nuclei to gain time to study their properties is something quite desirable. An alternative strategy to the use of constant volume simulations is to pin the nucleus to a heterogeneous solid substrate [100].…”
Section: Seeding Of Condensationmentioning
confidence: 99%